Immunocytological analysis of the Tn associated antigen 83D4 in serous effusions from patients with cancer: comparison with Tn soluble glycoprotein. Issue 5 (May 1995) - Beuzelin-Yvraut, M; Bourguignat, A; Phillips, E; Roseto, A; Osinaga, E
Abstract : AIMS–To determine whether the monoclonal antibody (MoAb) 83D4, previously shown to be highly specific for carcinoma cells, can be used as an immunocytological marker to discriminate between benign and malignant cells in serous effusions; and to test for a correlation between expression of the antigen reacting with MoAb 83D4 on effusion cells and the amount of soluble 83D4 antigen in effusion fluids. METHODS–Thirty three pleural and 23 peritoneal effusions from 56 cancer patients with metastatic disease were tested for the presence of Tn associated 83D4 antigen by immunocytochemical staining, and for the presence of soluble antigen in supernatants. The patients had undergone various chemotherapy and radiation therapy protocols. RESULTS–As a result of the various types of treatment, the cytological characteristics of the cells were often modified and the antigenic epitopes may have been altered. Positive staining for 83D4 MoAb was obtained in 36 (97%) of the 37 malignant effusions, eight (73%) of 11 suspect effusions, and three (38%) of the eight apparently benign effusions (free of malignant cells). In these latter cases, cytological reassessment showed a few suspect cells in two cases. 83D4 soluble antigen was detected in 30 of 37 malignant effusions (81%), five of 11 suspected infusions (46%), and five of eight apparently benign effusions (63%). CONCLUSIONS–Immunocytochemical staining with anti-83D4 antibody is useful for differentiating reactive or atypical mesothelial cells from epithelial cells, especially in breast cancer effusions.